​Benchmark workshop on horse mackerel and boarfish (WKBHMB) ... - ICES (ICES Scientific Reports, 2024)
The benchmark workshop on horse mackerel and boarfish (WKBHMB) evaluated the assessment (input data and methodology), short-term forecast procedures, and reference points for three horse mackerel stocks and one boarfish stock. A key focus has been on evaluating stock structure for horse mackerel making new data available for catches, surveys and CPUE, and applying new modelling approaches to the assessments of the stocks. General introduction to horse mackerel in the Northeast Atlantic (Section 2) The data call for WKBHMB led to a revision of the landings and discards data, and some additional survey and CPUE data, for the three horse mackerel stocks. Catch data were supplied by 14 countries and length sampling data and age–length keys were supplied by 7 countries. The majority of countries delivered data for the 2003–2022 period. Based on the periods covered by the data submissions to the benchmark, revised dataseries were compiled for the period 2003–2022. No revisions were made to the existing data for ...